Restoring economic equilibrium : human capital in the modernizing economy - "Schultz, Theodore" (Oxford, 1990)
Nobel Laureate Theodore W. Schultz has made important contributions to the fields of agriculture and natural resource economics, and to human capital theory. In this book, he builds on this seminal work to present an overview of the impact of modernization on the equilibrium of an economy. Beginning with small units - the entrepreneur, the family, the farmer, the researcher - he examines the foundations of economic growth on increases in income, how this growth causes disequilibria, and the means for a return to equilibrium. Critical of much of equilibrium economics the author focuses on three neglected areas in the study of growth. Firstly, he underlines specialization as the key to most modern increases in income; secondly, he explores the inevitable emergence of disequilibria as increases in income are realized from advances in technology, the proliferation of human capital and elsewhere; and finally, he explains the crucial role of entrepreneurs in restoring economic equilibrium.
Keywords: Economic development